THINK-PAIR-SHARE: A TECNIQUE TO ENHANCE STUDENTS’ WRITING SKILL - Okta Ika Rahmawati (Jurnal Pendidikan Edutama, 2017)
Abstract: Think – Pair Share: A Tecnique to Enhance Students’ Writing Skill. This article refers to a classroom action research on teaching writing by implementing Think-Pair-Share at High School in Bojonegoro. Think-Pair-Share Technique is a kind of cooperative learning technique. This technique encourages students to actively involve in the learning process since they have to discuss with their partner about the material being learned. The subject of the study was the tenth-grade students of SMAN 1 Bojonegoro. The result shows that the implementation of Think-Pair-Share in teaching writing can improve students’ skill in writing narrative text.Keywords: enhance, think-pair-share, writing skillAbstrak: artikel ini berisi tentang penelitian tindakan kelas pada pembelajaran menulis dengan menerapkan teknik Think-Pair-Share di SMAN 1 Bojonegoro. Think-Pair-Share adalaha salah satu teknik pembelajaran kooperatif. Teknik ini mendorong siswa untuk aktif berpartisipasi dalam proses belajar karena mereka harus berdiskusi tantang materi yang sedang diajarkan dengan temannya. Subjek penelitian ini adalah siswa kelas sepuluh SMAN 1 Bojonegoro. hasil penelitian menunjukkan bahwa penerapan Think-Pair-Share pada pengajaran menulis narrative text dapat meningkatkan kemampuan menulis siswa kelas sepuluh.Kata Kunci: peningkatan, think-pair-share, kemampuan menulis